Analisa Kerusakan Perkerasan Jalan Rigid Dengan Metode Bina Marga Dan Metode PCI (Pavement Condition Index) Studi Kasus Jalan Lintas Muara Tembesi – Muara Bulian - Ma’sum Fajri; Fakhrul Rozi Yamali; Emelda Raudhati; Fakhrul Rozi Yamali (Jurnal Talenta Sipil, 2022)
In analyzing the condition of rigid road damage, the Bina Marga method and the PCI (Pavement Condition Index) method can be used. This study aims to determine the level of road surface damage and how to handle it on the Muara Tembesi - Muara Bulian crossing, Simpang Terusan Village to Tenam Village, with a length of 2,850km and a pavement width of 7.5m. In this study, the priority order of road handling using the Bina Marga method is based on a range of values from 0 to 7, while the PCI method ranks pavement conditions from 0 to 100. The results of the assessment on the Muara Tembesi - Muara Bulian cross-road using the Bina Marga method and the PCI method (Pavement Condition Index) shows a relatively similar assessment, where the Bina Marga Method has the results that the left side with the priority order of UP = 4 and the right side with the priority order of UP = 5 and is categorized in the periodic maintenance program. While the PCI method (pavement condition index) has the result that the value of the level of damage to the left side is 88.21 and the right side is 94.78, which is included in the perfect qualification (excellent), so it is categorized in the periodic maintenance program.